Communication Competency Account Representative in Doing Tax Payer Compliance Supervision at Pelayanan Pajak Pratama Office Medan Timur - Raden, Hari (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The objective of the research was to analyze Account Representative communication competence, analyze how effective communication channels are carried out by Account Representatives, and analyze taxpayer tax compliance as the impact of AR communication competence in improving at KPP Pratama Medan Timur. Researchers used the descriptive qualitative research method by conducting data collection methods through in-depth interviews and documentary methods. Research subjects obtained 6 (six) informants who themselves are from Account Representatives and Taxpayers in the KPP Pratama Medan Timur. The results showed that the Account Representative's communication competence in supervising tax compliance to taxpayers at KPP Pratama Medan Timur was good because the Account Representative already had the components of communication competence in the form of motivation, skills, and knowledge. The most effective communication channel used by Account Representatives in supervising tax compliance to taxpayers is an interpersonal communication channel through the telephone network because messages are delivered quickly, but have few technical constraints, namely network constraints but not too often. Good communication competence possessed by the Account Representative can make taxpayers pay or report SPT, namely changing the attitude of taxpayers who initially have not paid tax payable or reporting SPT, so taxpayers are willing to carry out their tax obligations. With taxpayers paying and reporting tax returns, they can improve tax compliance of taxpayers at KPP Pratama Medan Timur